Tariffs, trade and productivity: a quantitative evaluation of heterogeneous firm models - Breinlich, Holger; Cunat, Alejandro (Wiley, 2015)
We examine the quantitative predictions of heterogeneous firm in the context of the Canada–US Free Trade Agreement (CUSFTA) of 1989. We compute predicted increases in trade flows and measured productivity and compare them to the post-CUSFTA increases observed in the data. Most models predict increases in measured productivity that are too low by an order of magnitude relative to predicted increases in trade flows. A multi-product firm extension that allows for within-firm productivity increases has the potential to reconcile model predictions with the data.